THE RELATIONSHIP BETWEEN THE MARKETING STRATEGIES OF CONTENT MARKETING, INFLUENCER MARKETING, AND TIKTOK SHOP ON TIKTOK, AND IMPULSIVE BUYING BEHAVIOR IN AMUNTAIHULU SUNGAI UTARA - Rossydah, Rossydah; Yudianto, Ary (PPPM STIA Amuntai, 2025)
The rapid expansion of digital media, particularly the TikTok platform, has transformed contemporary marketing strategies and had a notable impact on the shopping behavior of younger generations. This study explores the connection between various TikTok-based marketing tactics specifically Content Marketing, Influencer Marketing, and the integration of TikTok Shop features and the impulsive buying habits of youth in Amuntai, Hulu Sungai Utara. Employing a descriptive quantitative design, data were obtained through surveys distributed to 76 individuals aged 17–25 who actively use TikTok. The information collected via structured questionnaires was analyzed using multiple linear regression. The results demonstrate that both Influencer Marketing and TikTok Shop significantly and positively influence impulsive purchasing behavior, while Content Marketing shows no substantial relationship. These findings imply that emotionally engaging promotions and convenient digital transaction features are more effective in triggering unplanned purchases than simply delivering visually appealing content. This research emphasizes the importance of designing marketing efforts that appeal to both emotional resonance and user convenience, especially when targeting digital-native consumers. In conclusion, the study illustrates how the integration of social influence and efficient shopping tools offers a strategic edge in appealing to impulsive buyers in today’s digital environment.